Study of cirrus clouds physical properties over the state of São Paulo, Brazil, from CALIPSO/CALIOP level 2 data - Souza, Giovanni (2023)
Satellite measurements have made an enormous contribution to the development of scientific knowledge. By providing data on atmospheric components over large areas and long periods of time, these instruments have enabled researchers to gain a much deeper understanding of the environment. In this study, we analyzed level 2 data from the CALIPSO/CALIOP satellite to investigate the physical and optical characteristics of cirrus clouds in the state of São Paulo between 2007 and 2017. The study showed that cirrus is the most present type of cloud in the region, and they mainly form at altitudes between 10 km and 14 km, and average thickness of 1.4 km. They form at low temperatures, typically less than -40°C. The analysis of the seasonal characteristics showed that the frequency of occurrence of cirrus clouds increase during summer, and coincide with the formation of convective clouds due to the formation of cirrus from anvil clouds. The optical depth analysis revealed that the most common type of cirrus is thick (optical depth > 0.3), with a overall frequency of occurrence above 45%. These results provide valuable insights into the behavior of cirrus clouds in the region and demonstrate the important role that satellite measurements can play in advancing our understanding of the atmosphere.